Cannabis use, attitudes, regulation and health: Survey data from an urban population of users and non-users - Hansjörg Znoj (PAGEPress Publications, 2021)
Background: Although illegal in most countries, cannabis remains the most common illicit drug in Switzerland and worldwide. While there is growing evidence on adverse effects of cannabis use, most users do not report any problems or negative consequences. In the face of a sustained high prevalence of cannabis use and the recent legalization waves in different parts of the world, it is important to know how cannabis is perceived in the general population and how current users regulate their own use. The present study aims to investigate users’ and non-users’ attitudes towards cannabis regulations and towards current users. Additionally, self-rated health measures as well as protective behavioral strategies and other cannabis related variables were assessed. Design and Method: We collected data from 380 current users and 659 non-users who were recruited by invitation letter or online media platforms. The data was analyzed using basic descriptive statistical procedures. Results: Results revealed that both groups favor moderate cannabis regulation measures over prohibition and no regulation at all. On average, they report the same subjective health. Protective strategies are often used and are associated with better health and lower severity of dependence in cannabis users. Conclusions: Taken together, results indicate that safe use of cannabis is possible for most users, while there is a group of users at risk of 15-20 %, which may benefit from control by regulatory measures.